The Influence of Competence and Job Characteristics on Performance with Organizational Commitment as Mediation (A Study on Personnel of Satrad 212 Ranai and Satrad 245 Saumlaki) - Dewan Pujiantoro; Endang Tjahjaningsih (Jurnal Ekonomi Manajemen Sistem Informasi, 2026)
This study aims to analyze the effect of competence and work characteristics on performance with organizational commitment as a mediator at Satrad 212 Ranai and Satrad 245 Saumlaki. The research sample consisted of all 54 personnel at Satrad 212 Ranai and 52 personnel at Satrad 245 Saumlaki, for a total sample size of 106 individuals using a census sampling technique. The data analysis techniques used included descriptive analysis, instrument testing, model testing, hypothesis testing, and Sobel testing using SPSS 26 software. Based on the validity test, the results showed that the sample adequacy was met, and the indicators were valid and reliable. The results of the study showed that the hypothesis that competence has a positive and significant effect on organizational commitment, job characteristics have a positive and significant effect on organizational commitment, competence has a positive and significant effect on performance, job characteristics have a positive and significant effect on performance, and organizational commitment has a positive and significant effect on performance. The results of the Sobel test also show that organizational commitment mediates competency and job characteristics on performance.